Pengaruh Word Of Mouth, Harga, Dan Kualitas Layanan Terhadap Keputusan Pembelian (Studi Pada UD. Toko Bangunan Barokah Jaya Jombang ) - Amalia, Roikhana Nur; Farida, Eka; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of Word of Mouth, price, and service quality on purchasing decisions at UD. Toko Bangunan Barokah Jaya Jombang using a quantitative approach, with data collected through customer surveys. The results show that Word of Mouth has a positive and significant effect, emphasizing the importance of consumer recommendations in purchasing decisions, while price also has a positive and highly significant effect, indicating that competitive pricing can drive customer purchases. In contrast, service quality has a negative and significant effect, meaning the services provided have not met customer expectations. These findings suggest that Toko Bangunan Barokah Jaya should evaluate and improve service quality while maintaining effective pricing strategies. This study is expected to serve as a reference for business practitioners in designing targeted marketing strategies to increase sales. Keywords: Word Of Mouth, Price, Service Quality Purchase Decision